Zmienne hierarchiczne w pomiarze odległości w symbolicznej analizie danych - Pełka, Marcin (Taxonomic Variables in Symbolic Dissimilarity Measure in Symbolic Data Analysis, 2005)
The aim of this article is to present all types of dissimilarity measures in symbolic data analysis (such as Gowdy-Diday, Ichino-Yacuchi and De Carvalho measures) with problems which can be found in each of them while using specified variables types, especially taxonomic variables. Article presents polish suggestions for terms used in dissimilarity measures. For empirical examples analysis of car marked was used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 367-375